Case report: An unusual presentation of oral acute graft-versus-host-disease in a haploidentical hematopoietic stem cell transplant recipient - HSU LING CATHERINE HONG (ELSEVIER SCIENCE INC, 2021)
10.1016/j.oooo.2015.12.004